4‐Channel Sliding Mode Control of Teleoperation Systems with Disturbances. Issue 4 (11th September 2014) - Liu, Xia; Dong, Xiucheng
Abstract Sliding mode control can effectively account for the disturbances of a system. Among the different teleoperation architectures, 4‐channel architecture is the most successful for fulfilling transparency. In this paper, two sliding mode controllers are designed for nonlinear master and slave with external disturbances and are incorporated into a 4‐channel structure to achieve transparency. To this end, each of the controllers consists of a sliding mode position feedback law, a force feedback law, and two supplementary terms regarding gravity and contact force compensation. Stability and transparency of the overall system is studied via a Lyapunov function analysis. Simulations compared with the conventional adaptive control on teleoperation systems demonstrate the effectiveness of the proposed scheme.